2016
DOI: 10.1038/ng.3589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TMEM230 mutations in familial Parkinson's disease

Abstract: Parkinson’s disease is the second most common neurodegenerative disorder without effective treatment. It is generally sporadic with unknown etiology. However, genetic studies of rare familial forms have led to the identification of mutations in several genes, which are linked to typical Parkinson’s disease or parkinsonian disorders. The pathogenesis of Parkinson’s disease remain largely elusive. Here, we report a novel genetic locus for an autosomal dominant, clinically typical and Lewy body confirmed Parkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 47 publications
9
167
3
1
Order By: Relevance
“…They also showed that TMEM230 encodes a transmembrane protein of synaptic vesicles in neurons and that disease-linked mutations impair synaptic vesicle trafficking. Presence of TMEM230 in alpha-synuclein-positive Lewy bodies and Lewy neurites in midbrain and neocortex sections from sporadic PD cases gave supporting evidence for a role of this gene in PD pathology (Deng et al, 2016). …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…They also showed that TMEM230 encodes a transmembrane protein of synaptic vesicles in neurons and that disease-linked mutations impair synaptic vesicle trafficking. Presence of TMEM230 in alpha-synuclein-positive Lewy bodies and Lewy neurites in midbrain and neocortex sections from sporadic PD cases gave supporting evidence for a role of this gene in PD pathology (Deng et al, 2016). …”
Section: Introductionmentioning
confidence: 88%
“…In a recent publication, Deng et al showed genetic evidence linking a mutation in transmembrane protein 230 ( TMEM230 ) to autosomal dominant Parkinson’s disease (PD) in a large family from North America (Deng et al, 2016). Identification of an additional mutation in 7 small Chinese families supports their results and suggests that mutations in this gene may be a relatively common cause of PD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…27 Unsurprisingly, there are numerous examples of variant TMEM proteins in human genetic disorders, [28][29][30][31][32][33][34] and in that context, we do gain pathomechanistic clues about the disorder. We have reported enrichment of TMEM domains in the ciliary proteome, 35 raising the possibility that the present constellation of phenotypes could be part of the ciliopathy spectrum.…”
Section: Renal Defectsmentioning
confidence: 99%
“…Concerning the monogenic forms of PD were found mutations in 7 genes of AD transmission (SNCA, LRRK2, GIGYF2, VPS35, EIF4G1, HTRA2, TMEM230) and even more in those of AR transmission. Recent data provide evidence for new molecular pathways involving neurodevelopmental mechanisms [207,210], modulating the signaling processes at the endocytic pathway [142], synaptic vesicles endocytosis and trafficking in PD pathogenesis [202,206], maintaining the integrity of the cytoskeleton and axonal transport in neurons [192].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, another gene with role in synaptic vesicle trafficking involved in pathogenesis of PD was identified on chromosome 20pter-p12 [206]. TMEM230 codes for a transmembrane protein of secretory/recycling vesicles.…”
Section: Tmem230mentioning
confidence: 99%